Epidemiological profile of Staphylococcus spp. isolated from hemocultures of interned patients in a tertiary attention hospital of the Ceará public network - Aguiar, Ana Luiza Ribeiro (2021)
Staphylococcus spp. has been highlighted among bloodstream infections (BI), presenting high prevalence, multidrug resistance and considerable lethality. The present study aimed to analyze the prevalence and the susceptibility profile of Staphylococcus spp. isolated from positive blood cultures from a tertiary care public hospital of Ceará, from January 2015 to December 2018. Of the 3292 blood cultures performed during this period, only 15.88% were positive, of which 24.85% were Gram positive cocci. S. aureus represented 1.53% of positive blood cultures, of which 50% were oxacilin resistant. Isolates of coagulase-negative Staphylococcus spp. showed a prevalence of 10.89%, represented by: S. epidermidis (n = 23), S. haemolyticus (n = 17), S. hominis (n = 13), S. saprophyticus (n = 2) and S. warneri (n = 2). Multiresistance occurrence was verified in several of the analyzed isolates, presenting intra and inters species variations. Therefore, our findings improve the understanding of the epidemiology of BI caused by Staphylococcus spp. in the studied institution, as well as its susceptibility profile. Early identification of the infectious agent might aid in the appropriate choice of treatment, increasing the chance of cure and reducing the patient length stay in hospital.